2019
DOI: 10.1096/fj.201901259r
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of Babesia microti lactate dehydrogenase BmLDH reveal a critical role for Arg99 in catalysis

Abstract: The tick-and transfusion-transmitted human pathogen Babesia microti infects host erythrocytes to cause the pathologic symptoms associated with human babesiosis, an emerging disease with worldwide distribution and potentially fatal clinical outcome. Drugs currently recommended for the treatment of babesiosis are associated with a high failure rate and significant adverse events, highlighting the urgent need for more-effective and safer babesiosis therapies. Unlike other apicomplexan parasites, B. microti lacks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Our previous study based on the crystal structures of BmLDH indicated that the mutation of residue Arg99 to Ala significantly reduced the enzyme activity of BmLDH (up to 86%), but had no impact on Human LDH-A (Yu et al, 2019). For testing the probability of BmLDH as a selective drug target, the potent inhibitors interacting with the residue Arg99 were screened via a molecular docking based on the crystal structure of BmLDH from a series of gossypol derivatives or structural analogs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study based on the crystal structures of BmLDH indicated that the mutation of residue Arg99 to Ala significantly reduced the enzyme activity of BmLDH (up to 86%), but had no impact on Human LDH-A (Yu et al, 2019). For testing the probability of BmLDH as a selective drug target, the potent inhibitors interacting with the residue Arg99 were screened via a molecular docking based on the crystal structure of BmLDH from a series of gossypol derivatives or structural analogs.…”
Section: Resultsmentioning
confidence: 99%
“…In Babesia bovis, gossypol inhibited BbLDH enzymatic activity to cause the death of B. bovis and its K i and IC 50 in vitro values were determined as 0.085 and 50 mM (Bork et al, 2004). In B. microti, the catalytic activity of BmLDH was inhibited by gossypol at 0.67 mM (K i ), and the IC 50 value of gossypol against B. microti in vitro was 7.07 mM (Yu et al, 2019). Previous studies showed that these derivatives of gossypol exhibited obviously lower cytotoxicity toward mammalian cells than the parent compound (Royer et al, 1991;Royer et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the enzymatic activity of purified rBmPYKI, the GST tag was removed from the recombinant protein; and the indirect coupled lactate dehydrogenase (LDH) assay was applied. Recombinant B. microti LDH (rBmLDH) protein, the only one isoform in B. microti , was expressed and purified according to previously published protocol ( Yu et al, 2019 ). The standard enzyme kinetic assay was conducted by monitoring the decrease in NADH at a wavelength of 340 nm using a microplate reader (BioTek, Winooski, VT, United States).…”
Section: Methodsmentioning
confidence: 99%
“…In B. bovis , phenolic aldehyde gossypol dramatically inhibited the catalysis activity of BbLDH with a K i value of 0.85 μM, and the value was lower than human LDH-A (HuLDH-A) (1.9 μM) and CpLDH (14.9 μM)), and similar to PfLDH (0.7 μM) and BmLDH (0.67 μM). Interestingly, gossypol treatment also reduced the in vitro growth of these parasites with IC 50 values of 50 μM for B. bovi s, 15.3 μM for P. falciparum , 11.8 μM for C. parvum , and 7.07 μM for B. microti ( Yu et al., 2001 ; Bork et al., 2004 ; Choi et al., 2007b ; Zhang et al., 2015 ; Yu et al., 2019 ). These reports suggest that LDHs of apicomplexan parasites might act as a future drug candidate for finding new anti-parasitic drugs.…”
Section: Introductionmentioning
confidence: 99%